Jewish Theme in Diaries and Travel Notes of Christian Pilgrims who Visited Palestine in Late 19th - Early 20th Centuries - I. S. Dushakova (Научный диалог)
Travel notes and diaries of Christian pilgrims who visited Palestine in the late 19th - early 20th centuries are studied. Text fragments containing references to Jews are analyzed. The novelty of the research is seen in the fact that ego-documents are considered not as a source of historical data about the pilgrimage, but as written evidence of ideas about other ethnic / religious groups that existed in the specified period. The relevance of the study is due to the fact that the mechanisms of differentiation of “own” and “other” are revealed. It is proved that the Jews are those actors in relation to whom self-identity of Christian pilgrims from the Russian Empire is strengthened if not built. The content analysis is carried out according to the thematic blocks and motives identified in those fragments of diaries and travel notes that contain references to Jews. The author comes to the conclusion that for Christian pilgrims who went to Palestine, Jews played the role of “generalized others.” Significant symptoms of alienation were the distinctive features of the Jews: the attitude to money and the occupied space, the manner of behaviour in public places. It is revealed that religious differences were less important for pilgrims.